PARTISIPASI MASYARAKAT PADA PELESTARIAN RUMAH ADAT ACEH DI DESA WISATA LUBOK SUKON ACEH BESAR - Wira Fikria; Mirza Irwansyah; Renni Anggraini (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2019)
Indonesia has traditional architecture and traditional custom house that are specific and varied according to locally aplicable tradition, one of them is traditional house located in Aceh province called Acehnese house or rumoh Aceh. Lubok Sukon Village in Aceh Province is one of the village that still maintains the Acehnese houses as the residency and phisically as the identity of its region. The current development of residence is more directed to be current modern model of houses. This  will threaten the existency of Acehnese houses sustainability and will impact to the physical of its historical area, therefore an effort to preserve the Acehnese traditional housesis needed through community participation so that a sustainable preservation concept can be realized. The metodology applied in this research is qualitative and quantitativecombination method (mixed method) with descriptive analysis. The result of the research shown that the community participation on Acehnese houses preservation is still high based on their concern and interest along with their eagerness to maintain the existency of Acehnese traditonal houses by 82.5%. This is also in accordance with the conditions of the Acehnese housesalthough some traditional elements of the house have undergone changes, but visually the identity of Acehnese houses generally remains visible. The development of Acehnese houses preservation in Lubok Sukon is not only covered the building arrangements, but also the environment of village area.